Costs and effectiveness of ciprofloxacin and ceftriaxone in treatment of typhoid fever in children in Thailand. - Wannee Limpitikul; Phechnoy Singchungchai (Universiti Kebangsaan Malaysia, 2013)
The burden of typhoid fever remains high in impoverished settings, and increasing antibiotic resistance is making treatment costly. The purposes of this study were: to compare the costs and the effectiveness of typhoid programs between oral and injection treatments in pediatric patients at Songkhla Hospital.